Effect of rapid EEG on anti‐seizure medication usage. Issue 5 (3rd November 2022) - Kurup, Deepika; Davey, Zachary; Hoang, Phuong; Wu, Connie; Werbaneth, Katherine; Shah, Varun; Hirsch, Karen G.; Govindarajan, Prasanthi; Meador, Kimford J.
Abstract: Objective . To study how early diagnoses from rapid EEG (rEEG) during the initial evaluation of patients with suspected non‐convulsive seizures correlates with changes in anti‐seizure medication (ASM) use. Methods . We performed a retrospective chart review of 100 consecutive adult patients at an academic medical center who underwent rEEG monitoring for suspected non‐convulsive seizures. We collected information on the timing of ASM administration and categorized EEG diagnoses as seizures (SZ), highly epileptiform patterns (HEP), or normal or slow activity (NL/SL). We used a χ 2  test to determine whether the use of ASMs was significantly different between SZ/HEP and NL/SL cases. Results . Of 100 patients, SZ were found in 5%, HEP in 14%, and no epileptiform/ictal activity in 81%. Forty‐six percent of patients had received ASM(s) before rEEG. While 84% of HEP/SZ cases were started or continued on ASMs, only 51% of NL/SL cases were started or continued on ASMs after rEEG (χ 2  [1, n =100] = 7.09, p =0.008). Thirty‐seven patients had received sedation (i.e., propofol or dexmedetomidine) prior to rEEG. In 15 patients (13/30 NL/SL, 2/7 HEP/SZ), sedation was discontinued following rEEG. Significance . Our study demonstrates that seizures were rapidly ruled out with rEEG in 81% of patients while 19% of patients were rapidly identified as having seizures or being at higher risk for seizures. The rapid evaluation of patients correlated with a significant reduction in ASM treatment in NL/SL cases compared to HEP/SZ cases. Thus, early access to EEG information may lead to more informed and targeted management of patients suspected to have nonconvulsive seizures.